Development of a Best Evidence Statement for the Use of Pressure Therapy for Management of Hypertrophic Scarring. Issue 4 (July 2016) - Sharp, Patricia A.; Pan, Brian; Yakuboff, Kevin P.; Rothchild, Dawn
Abstract : Pressure therapy has been considered standard, first-line intervention for the treatment of hypertrophic scars since its introduction in the 1960s. Although widely used, this scar management technique has historically been based on a wide array of anecdotal evidence as opposed to strong scientific support. Evidence has become more prevalent in recent years, necessitating a synthesis to develop an evidence-based clinical guideline. The clinical question was asked, "Among individuals with or at risk to develop active hypertrophic scars, does treatment with pressure therapy improve aesthetic and functional outcomes?" An evidence-based practice project was completed with aims to synthesize relevant literature to determine recommendations for the use of pressure therapy in individuals at risk for hypertrophic scars. A systematic search of the literature was conducted for the dates January 1950 to February 2014 of the following databases: MEDLINE, CINAHL, Cochrane Database for Systematic Reviews, Burntherapist.com, Cochrane Libraries, Ebsco, Google Scholar, OT Seeker, Ovid, MedLine, PEDro.org, Pubmed.gov, Pubmed Clinical Queries, and hand search of relevant articles through use of reference lists. Search terms included scar, hypertroph*, pressure therapy, compression therapy, pressure garment, burn, scald, trauma as well as MeSH terms cicatrix and hypertrophic. Articles were reviewed in terms of ability to answer the clinical question as well as strength of conclusions. A total of 45 articles were found and critiqued, 28 of which were relevant to the clinical question. Evidence strength ranged from level 1 to level 5. Results from the studies were synthesized to create clinical recommendations to guide treatment. Based on best available evidence, it is recommended that pressure therapy is utilized to decrease scar height and erythema that it is used for grafts and wounds requiring 14 to 21 days to heal, for 23 hours/day for 12 months, fit to achieve 20 to 30 mm Hg of pressure, fit by a skilled technician, and replaced every 2–3 months. In addition, it is not recommended that pressure therapy is used to treat abnormal pigmentation, nor used to hasten scar maturation. This literature search revealed insufficient evidence addressing the impact of pressure therapy on scar pliability. Among individuals with or at risk to develop active hypertrophic scars, treatment with pressure therapy does improve outcomes, particularly for aesthetic concerns including scar thickness and erythema. Applicability of research to practice: The practical treatment recommendations presented may improve consistency and efficacy of pressure therapy utilization at the point of care.